Do Shareholders Assess Managers' Use of Accruals to Manage Earnings as a Negative Signal of Trustworthiness Even When Its Outcome Serves Shareholders' Interests?* - Hewitt, Max; Hodge, Frank D.; Pratt, Jamie H. (Contemporary Accounting Research, 2020)
ABSTRACT We examine how shareholders' trust in managers is affected by (i) the outcome of earnings management (inconsistent vs. consistent with shareholders' interests) and (ii) the method of earnings management (accruals vs. real methods). Using a controlled experiment, we predict and find that trust is impaired when the outcome of earnings management suggests that managers have put their interests above shareholders' interests and/or when the method of earnings management suggests that managers misreported the firm's economic performance. We argue that shareholders assess managers putting their interests above shareholders' interests as a signal of untrustworthiness because it involves a transfer of the firm's resources away from shareholders to managers. We argue that shareholders also assess managers' use of accruals to manage earnings as a signal of untrustworthiness because, in this instance, managers misreport the firm's economic performance. Finally, we show that trust mediates the combined effects of the outcome of earnings management and the method of earnings management on investment decisions. Our study incrementally contributes to the literature by highlighting the adverse implications of managers' use of accruals to manage earnings even when its outcome serves shareholders' interests.